2022
DOI: 10.46827/ejes.v9i10.4476
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Education and Pedagogy: A Practice for All Students

Abstract: Inclusion is an approach and procedure with philosophical, political, educational and social dimensions. The aim of inclusive education is to eliminate school and social exclusion. The framework places schools are at the centre of inclusive education. In this context, inclusive pedagogy refers to the ways that courses, classroom activities, curricula, and assessments consider issues of diversity in an effort to engage all students in learning that is meaningful, relevant, and accessible. This article constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the context of the present research, it is worth noting that the teacher in the contemporary school is called upon to utilize teaching practices and techniques, such as experientialparticipatory teaching techniques, which go beyond formalistic standards, prioritize the communicative nature of teaching and utilize flexible processes, focusing on the educational needs, learning readiness and multiple intelligences of students (Başaran, 2021;Dimitriadou, 2016;Ioannidi & Malafantis, 2022;Kalantzis & Cope, 2012;Malafantis, 2022;Peko & Varga, 2014). In other words, in this case, if the teacher utilizes participatory teaching techniquessuch as brainstorming -the teacher will be able during teaching to meet the needs and interests of students, their learning profile , involving them in an active and experiential way in the teaching and learning process (Evangelou, 2023a;Barta et al, 2022;Grigoriadou et al, 2009;Linsenmeyer, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the present research, it is worth noting that the teacher in the contemporary school is called upon to utilize teaching practices and techniques, such as experientialparticipatory teaching techniques, which go beyond formalistic standards, prioritize the communicative nature of teaching and utilize flexible processes, focusing on the educational needs, learning readiness and multiple intelligences of students (Başaran, 2021;Dimitriadou, 2016;Ioannidi & Malafantis, 2022;Kalantzis & Cope, 2012;Malafantis, 2022;Peko & Varga, 2014). In other words, in this case, if the teacher utilizes participatory teaching techniquessuch as brainstorming -the teacher will be able during teaching to meet the needs and interests of students, their learning profile , involving them in an active and experiential way in the teaching and learning process (Evangelou, 2023a;Barta et al, 2022;Grigoriadou et al, 2009;Linsenmeyer, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to Plomp, [32] modern school is no longer the only "body" for disseminating knowledge but one among several others where traditional and new means of education are combined [33] [34] [35] [36] [37] [38] [39]. Nowadays schools must properly support and educate students with creative activities [40] keeping their interest in a variety of ways in an educational environment that respects their individuality and diversity.…”
Section: Special Needs and Educationmentioning
confidence: 99%
“…For this reason, it is often observed that instead of enjoying high scores on the assessment, they are ranked among students with low grades [74]. Thus, inclusive education and pedagogy for these students is believed to be one of the most effective ways since the aim of inclusive education is to eliminate school and social exclusion [75].…”
Section: Necessity and Possibility Of Educating "Charismatic" Studentsmentioning
confidence: 99%
“…Teaching is a complex and multi-interpretive concept, which depends on the social, cultural and ideological background of each era and society in which it is studied (Dimitriadou, 2016;Gay, 2018;Tzifopoulos, 2021). Contemporary developments in the field of education shaped by the increasing cultural heterogeneity of the student population, the integration of new technologies in school and the diversification of the needs of the modern student constitute a new educational reality that requires new educational and teaching adaptations in teaching and learning in the classroom (Başaran, 2021;Ioannidi & Malafantis, 2022;Kalatzis & Cope, 2013;Malafantis, 2022;Bayati, 2015).…”
Section: Introductionmentioning
confidence: 99%